1933 Haw. Sess. Laws 39 - (:unkn) unknown (My University, 1933)
An Act Regulating the Sale, Transfer, and Possession of Firearms and Ammunition, § 8: Required license for concealed carry of pistol, firearm, or ammunition; prohibits issuance of license to felony convicts or mentally ill; violators subject to fine or imprisonment.
Keywords: CARRY - CONCEALED